The Effect Of Occupational Health And Safety Programmes On Employee Productivity In The Mining Industry - Bando, Epina Felizita (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The implementation of occupational safety and health has the potential to affect employee productivity in a mining area. The study aims to determine the application of occupational safety and health in the production area, employee work productivity, and the effect of the application of occupational safety and health on employee work productivity at PT Bumi Sentosa Jaya. This research location is located in Boedingi Village, Lasolo District, North Konawe Regency, Southeast Sulawesi Province. The research method begins with data collection, analysis and data testing. Data collection in this study was carried out by distributing questionnaires to 42 employees in the production area and the data analysis techniques used were descriptive analysis techniques, multiple correlation tests, multiple linear regression analyses, partial tests (t tests), simultaneous tests (f tests) and the coefficient of determination. The results of this study indicate that the overall application of occupational safety and health is classified in the good category with an occupational safety value of 134.08; occupational health value 134.06; and employee work productivity with a value of 136.08. The application of occupational safety and health affects employee work productivity with an influence of 32.1%.